Circadian Rhythms in Fungi: Structure/Function/Evolution of Some Clock Components. Issue 4 (August 2019) - Brody, Stuart
The fungal clock, especially that in Neurospora crassa, is composed of several proteins, notably FRQ, WC-1, and WC-2, which interact at the protein level and at the level of transcription. It is shown here that regions of the FRQ that are highly conserved in many fungal species show significant similarity to regions of proteins found in the amoebae Capsaspora and Acanthamoebae. These 2 amoebae were specifically explored because they have been suggested, based on extensive evidence, to be related to precursors of the modern fungi. Those proteins in Capsaspora/Acanthamoebae with some similarity to FRQ are LARP (an RNA-binding protein), ARNT (which has a PAS motif), and heat shock factor (HSF). These regions of LARP and HSF that show similarity to FRQ are highly conserved between plants, animals, and amoeba. This suggests that these regions were present at the time of the divergence of plants, fungi, insects, and animals, and therefore, they could be plausible precursors to regions of the fungal FRQ. These particular regions of FRQ that show similarity to LARP and HSF are also of functional significance since mutations in these regions of the Neurospora FRQ led to changes in the rhythm. The FRQ proteins from 13 different species of fungi were analyzed via motif analysis (MEME), and 11 different motifs were found. This provides some understanding as to the minimum requirements for an FRQ protein. Many of these FRQ motifs can be matched up with known domains in FRQ. In addition, these 13 different species of fungi were screened for the presence/absence of 7 additional genes/proteins that play some role in fungal clocks.